Extending platinum-free interval in partially platinum-sensitive recurrent ovarian cancer by a non-platinum regimen: Its possible clinical significance - Yin-Ting Chuang; Chih-Long Chang (Elsevier, 2012)
Response to platinum retreatment in recurrent epithelial ovarian cancer is related to the platinum-free interval (PFI). The recommended and most accepted chemotherapy in the treatment of platinum-sensitive (PFI > 6 months) recurrence is platinum-based combination regimens. Patients with a PFI of 6-12 months are often considered partially platinum-sensitive (PPS) because lower response rates to subsequent platinum retreatment have been identified. Controversies and uncertainties still exist in this population of patients regarding the best treatment and the most effective therapeutic agents. It is proposed that extending the PFI with non-platinum agents may enhance the response to and the outcome of subsequent rechallenge with platinum. In this review, we discuss the treatment for PPS recurrent ovarian cancer and the possible clinical significance of extending PFI with intent to improve the medical care of PPS recurrence.